Graves Disease Presenting Psychosis: a Case Report - Devina Sagitania; Agung Frijanto; Budi Yuwono (Faculty of Medicine, Universitas Airlangga, 2024)
Introductions: Graves' disease is the most common cause of hyperthyroidism. Neuropsychiatric manifestations may occur in thyroid disease. As the premier clinical manifestation of Graves disease, psychosis is highly uncommon; it was reported in 1% of cases. The major neuropsychiatric manifestations of hyperthyroidism are acute psychosis, dementia, apathy, agitation, mania, delusional behavior, and hallucinations, especially in older people. Psychosis is highly rare as the first clinical symptom of a grave disease. Case: A 48-year-old female with grave disease symptoms had been taken to the emergency department with psychotic manifestations. She had a three-month history of increasing irritability, increasing irrational talking, staying awake most of the night, muttering, night-time wandering, and poor personal hygiene. She was admitted to the hospital, and the laboratory investigations showed an elevated FT4 and a decreased thyroid-stimulating hormone (TSH). The patient was started on propanolol 3 x 10 mg, propylthiouracil 3 x 50 mg tab, risperidone 2x2mg, trihexylphenidil 2x2mg, lorazepam 1x2mg, and Zyprexa injection once, which showed improvement in psychotic symptoms. Conclusion: Graves' disease can present with neuropsychiatric manifestations such as psychosis, mania, or a combination of both. A detailed medical history and physical and psychiatric evaluation are necessary for diagnosing and giving adequate treatment. A detailed clinical evaluation, including thyroid function tests, could be recommended for all patients who showed psychotic symptoms. More research is needed to comprehend the pathophysiology underlying psychosis due to Graves' disease, so that it is expected that the management can be carried out properly.